2022
DOI: 10.1111/jvim.16390
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary hyperparathyroidism in a Miniature Horse using chemical ablation of abnormal parathyroid tissue localized by 3‐phase computed tomography

Abstract: A 15‐year‐old Miniature Horse mare with persistently increased plasma calcium (total and ionized) and serum parathyroid hormone concentrations was presented for suspected primary hyperparathyroidism. Ultrasonography of the thyroid region identified an enlarged heterogeneous mass axial to the right thyroid lobe suggestive of an enlarged parathyroid gland, which was further confirmed using sestamibi nuclear scintigraphy and 3‐phase computed tomography. Percutaneous ultrasound‐guided ethanol ablation of the mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Percutaneous ultrasound‐guided ethanol ablation has been described in humans, dogs and horses; however, it is regarded as a second‐choice treatment with limited advantages over surgery. Current recommendations for ethanol ablation are for use in cases with a solitary parathyroid tumour with major contraindications for surgical treatment, as there are increased risk of morbidities including recurrent laryngeal nerve damage secondary to extravasation of ethanol and difficulty of subsequent surgical dissection due to development of peritumoural fibrosis (Colmer et al, 2022; Gear et al, 2005; Karstrup et al, 1990). Surgical management is the only curative treatment; however, there are many factors which may contribute to surgical failure including the presence of multi‐gland disease, misidentification of abnormal tissue on ultrasonography or scintigraphy, and misidentification of adenomatous tissue at surgery (Goldstein et al, 2003; Gorenberg et al, 2020; Jangjoo et al, 2017; Norman & Chheda, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous ultrasound‐guided ethanol ablation has been described in humans, dogs and horses; however, it is regarded as a second‐choice treatment with limited advantages over surgery. Current recommendations for ethanol ablation are for use in cases with a solitary parathyroid tumour with major contraindications for surgical treatment, as there are increased risk of morbidities including recurrent laryngeal nerve damage secondary to extravasation of ethanol and difficulty of subsequent surgical dissection due to development of peritumoural fibrosis (Colmer et al, 2022; Gear et al, 2005; Karstrup et al, 1990). Surgical management is the only curative treatment; however, there are many factors which may contribute to surgical failure including the presence of multi‐gland disease, misidentification of abnormal tissue on ultrasonography or scintigraphy, and misidentification of adenomatous tissue at surgery (Goldstein et al, 2003; Gorenberg et al, 2020; Jangjoo et al, 2017; Norman & Chheda, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous ultrasound-guided ethanol ablation has been described in humans, dogs and horses; however, it is regarded as a second-choice treatment with limited advantages over surgery. Current recommendations for ethanol ablation are for use in cases with a solitary parathyroid tumour with major contraindications for surgical treatment, as there are increased risk of morbidities including recurrent laryngeal nerve damage secondary to extravasation of ethanol and difficulty of subsequent surgical dissection due to development of peritumoural fibrosis (Colmer et al, 2022;Gear et al, 2005;Karstrup et al, 1990). Surgical management is the only curative treatment;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sensitivity of Tc-99 m sestimibi nuclear medicine scans for detecting parathyroid adenomas in horses is unknown, it has been reported to be approximately 90% in humans (Hillyar et al, 2022) and 17% in dogs (Matwichuk et al, 2000). In addition to the report in this issue (Connard et al, 2023), Tc-99 m sestimibi scintigraphic scanning has been reported to be effective in 13 of 16 (81%) previously published cases (Colmer et al, 2022;Cottle et al, 2016;Gorenberg et al, 2020;Tomlinson et al, 2014;Wong et al, 2004). Three quarters of human patients are asymptomatic and do not exhibit symptoms that are explained by PHPT, the clinical course of which has been described as being rather benign (Miedlich et al, 2002).…”
mentioning
confidence: 87%
“…Unless an abnormal hyperfunctioning parathyroid gland can be identified and its location defined, surgical removal (parathyroidectomy) or chemical ablation with ethanol may not be possible (Colmer et al, 2022). Whereas surgical treatment (parathyroidectomy) is recommended and curative for patients with both clinical disease and asymptomatic disease in the absence of comorbidities, medical treatment can be employed.…”
mentioning
confidence: 99%